Elaboración del sistema de gestión de calidad para la obtención del certificado ISO 9001-2008 de la empresa purifluidos Cía. Ltda., ubicada en el sector de la Carolina de la ciudad de Quito, provincia de Pichincha. - Ñacato Taco, Carlos Ramiro (2013)
This work has been based on the development of the quality manual which is the beginning of any Quality Management process, for which the information was raised from the different Purifluidos’ areas. It began with the development of operating manuals on all charges, which helps to potential staff changes happen and they are no longer so shocking at the company as previously. We defined professional profiles that are currently in each area and defined his current role with this information is up the quality manual along with General Manager guidelines specifying the policy to present to their customers. In this paper we present attached internal documents which they have been designed for control of the quality management system and start generating documentation for the pre-audit of PAF headquarters.